Determinants of Contraceptive Behaviours of Female Students in South-South, Nigerian Universities - Achalu, Dorathy I.; Achalu, Onuegbu E. (Advances in Social Sciences Research Journal, 2015)
The study is aimed to find out the determinants of contraceptive behaviours of female undergraduate students in South-South, Nigerian Universities using demographic variables of age, place of residence, year of study in the university and pattern of drug use. Four research questions and four hypotheses were raised to guide the study. Descriptive survey design was used for the study. The population for the study comprised 40,800 female undergraduate student studying in the ten government owned universities. A simple random sampling technique was used to draw 2,040 female students from the six universities. A questionnaire tagged “Determinants of Contraceptive Behaviours of Female Student Questionnaire” (DCBFSQ) was used for the collection of data. The reliability coefficient index of the instrument was 0.72. Frequencies, ANOVA, t-test and Multiple Regressions were used to analyse data obtained. Decisions were taken at a 0.05 level of significance. The results showed that the contraceptive behaviours of female students in the South-South Nigerian universities were significantly determined by age, place of residence, year of study in the university and pattern of drug use. Based on the findings, the following recommendations were made: reproductive health education should be made part of general course study for all years I and II students in Nigeria universities. This would help provide contraceptive knowledge that would help influence positive contraceptive behaviours. Counseling units should be established in the Student Affairs Department of all universities to offer counseling services on women reproductive health with emphasis on contraception. Health centres in the universities should provide family planning services to female students.